2021
DOI: 10.1002/ange.202014194
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Molecule Conductance of 1,4‐Azaborine Derivatives as Models of BN‐doped PAHs

Abstract: The single‐molecule conductance of a series of BN‐acene‐like derivatives has been measured by using scanning tunneling break‐junction techniques. A strategic design of the target molecules has allowed us to include azaborine units in positions that unambiguously ensure electron transport through both heteroatoms, which is relevant for the development of customized BN‐doped nanographenes. We show that the conductance of the anthracene azaborine derivative is comparable to that of the pristine all‐carbon anthrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…For model structure 1 , we found that 12 % of the recorded traces contain a clear molecular conductance signal that gives rise to two conductance clouds in the 2D histogram representation (Figure 4a). A further subdivision of the traces was performed using an unsupervised k‐means clustering process [28] (Figure 4b) which shows that the two clouds arise from independent set of traces. Generally, there is only one plateau per trace (examples of individual plateaus are shown in the Supporting Information, Figure S17).…”
Section: Resultsmentioning
confidence: 99%
“…For model structure 1 , we found that 12 % of the recorded traces contain a clear molecular conductance signal that gives rise to two conductance clouds in the 2D histogram representation (Figure 4a). A further subdivision of the traces was performed using an unsupervised k‐means clustering process [28] (Figure 4b) which shows that the two clouds arise from independent set of traces. Generally, there is only one plateau per trace (examples of individual plateaus are shown in the Supporting Information, Figure S17).…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, González and co‐workers designed and synthesized boron‐containing acenes 99 and 100 as model compounds for studying their single‐molecule charge transport properties (Figure 12a). [ 90 ]…”
Section: Optoelectronic Applicationsmentioning
confidence: 99%
“…However, this also perturbs the molecular architecture and the estimation of structural and electronic inuences isolated from each other is complicated. 33 Therefore, the doping with neighboring boron-nitrogen (BN) units has emerged as a popular strategy especially for planar PAHs, [35][36][37][38] as it provides isoelectronic and isostructural BN-PAHs. In such compounds, the disparities in properties are almost exclusively caused by altered electronegativities of the heteroatoms, 39 facilitating the comparison with the parent, allcarbon CC-PAHs.…”
Section: Introductionmentioning
confidence: 99%